Tingkat Pengetahuan Remaja Putri Tentang Pemeriksaan Payudara Sendiri (Sadari) untuk Deteksi Dini Kanker Payudara - bilqis fadhilah (Sinar : Jurnal Kebidanan, 2021)
Objective:  The purpose of this research knowed the level of konwoledge young women about SADARI for early detection of breast cancer Methods: This study use descriptive with cross sectional design. Population in this study is young woman at class X, XI, and XII of Senior High Scool of Muhammadiyah 7 Surabaya. Sampel taken by total sampling with 40 student. Data were collect by quetionare.    Results:   Result indicate that knowledge of girl adolescent about SADARI in Senior High School Muhammadiyah 7 Surabaya less than 80%. To overcome the low knowledge of young women about the early detection of breast cancer, we neet to give the counseling about SADARIConclusion:  we can collaborate with health worker and community health worker to improve the knowledge  about SADARI